The Spectrum of Preaching - Johnson Raih (Sekolah Tinggi Teologi Bandung, 2024)
When the question is asked, “What is Preaching?” various responses are possible. While some may try to describe its essential contents, others may describe the various methods of sermonic construction and the various genres in preaching. However, the aim of this article is to discuss the four viewpoints of preaching and then categorise them in a spectrum. To achieve that, it engages with the philosophy, nature, theology and practice of preaching.